Processos educativos em práticas comunicativas de radiodifusão comunitária: potenciais ambientes de produção de sentidos na perspectiva da heteroglossia - Cocco, Ricardo (2019)
The media are composed in mediators by whom they relate, understand and mean what surround them, because they are configured as spaces where senses are produced, built and rebuilt, where narratives are negotiated and arguments through the interpretation of the world take place. To put this research to the test, we chose radio, understood as a media platform that provides the experience of listening, speaking, imagining, and dialogue about daily life. Community Broadcasting is the specific subject (ComBro) as a phenomenon in movement and in constant transformation, that is configured like a field of fights involving diverse actors. It is assumed that each ComBro experience constitutes a universe of languages, codes and practices, under a plurality of articulated rhythms and logics, in each culture, region, locality and in certain contexts and, as a rule, arise from nonconformity in the face of several situations of injustice, oppression, exclusion and silencing. The main question that is tried to answer is: under which conditions the experiences of Community Broadcasting, situated in cultural and historical-social scenarios, compose environments of sense production in the heteroglossia perspective. Under the egis of a socio-historical approach, an exploratory and descriptive study of bibliographical and documentary character is presented, in order that these alternative communicative practices can be understood in interlocution with history and culture, from the subjects and contexts that give them intelligibility and materiality. Bakhtin's contribution (2009, 2011) is sought in the effort to understand the mediatic processes considering the production of meanings and the conditions of possibility of the heteroglossia that are generated by them. In a second moment, we present a field investigati on in which two experiments of ComBro were observed: the Radio Liberdade of the county of Tres Palmeiras and Community Radio of Frederico Westphalen county, both located in northern Rio Grande do Sul State. Based on the case study as a research method, data were produced from a triangulation of sources: interviews with broadcasters and managers, public opinion polls with the audiences and the elaboration of listening diaries about the broadcasters' schedules. The theoretical parameters of the Dialogical Analysis of Speech (DAS) are adopted for the analysis of the data, of Bakhtinian orientation. The results indicate that these communicative and communitarian practices, even in the midst of the vicissitudes and contradictions to which they are exposed, have the potential to promote discursive situations marked by heteroglossia. This occurs when they establish closeness to what is involved in people's lives; when they promote communicative experiences that give support so that the most diverse voices echo in the social dialogues; when there are reverberating spaces of mobilizing tensions and dissonant points of view; when they present a transgressive potential for discursive standardization and conventional communication logics; when they constitute scenarios of confrontation and processes of resistance and when they make political-ideological option by the peripheral and marginalized discourses. Discursive situations do not constitute heteroglots only and exclusively by the license or permission that they grant to the voices so that they participate in the processes of production of meaning, neither by the absence of conflicts and social pressures, but by the way they respect and celebrate the multiplicity and the architecture that they offer for them to dialogue. The pedagogical relevance of these alternative media resides in the modes of interaction that they can provide, in the possibilities of interlocution they are capable of and when they are able to construct favorable environments so that the positions of the speakers enter a plural discursive scenario and participate actively in the constitution of the directions. Plurality that, publicly manifested, enriches the human experience as a whole and the life of each one.